Penerapan Teknik Kuratul Kalam untuk Meningkatkan Keterampilan Berbicara Siswa pada Mata Pelajaran Bahasa Arab di Madrasah Ibtidaiyah: speaking skills; arabic language; kuratul kalam tehnique - Zakiyah, Nisa; Salahudin, Anas; Rahman, Alvin Yanuar (TADRUSUUN: JURNAL PENDIDIKAN DASAR, 2025)
This study is to evaluate the use of the Kuratul Kalam technique in enhancing the speaking abilities of fourth-grade pupils at MIN 2 Bandung. This study, driven by the inadequate speaking proficiency of students in Arabic language classes, employs the Classroom Action Research (CAR) methodology, utilising data collection approaches such as observation, performance assessments, and documentation. The employed data analysis methods were qualitative and quantitative methodologies. This study's results demonstrate that the implementation of the Kuratul Kalam approach can markedly enhance pupils' speaking abilities. During the pre-cycle, the mean score was 55.89, accompanied by a classical mastery percentage of 14%. In Cycle I, the mean score was 66.79, accompanied by a classical mastery percentage of 46%. In Cycle II, the mean score increased to 75.36, with a classical mastery percentage of 82%. This project aims to enhance students' speaking proficiency, particularly in Arabic language courses